The Effect of the Time Token Type Cooperative Learning Model on Learning Activeness and Student Learning Outcomes in Class VII Number Pattern Material at Sultan Iskandar Muda Private Middle School Medan - Eka Noviasari; Waminton Rajagukguk (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine whether there was a positive and significant effect between the time token type cooperative learning model on student activity and learning outcomes. This type of research is a quasi-experimental design with the Pretest-Posttest Control Group Design. The population in this study were all students class VIII SMP Swasta Sultan Iskandar Muda Medan which consisted of 6 classes. The sample in this study was class VIII-C as the experimental class with 33 students given the application of the time token type cooperative learning model and class VIII-B as the control class with 33 students given the application of the conventional learning model. The instrument in this study was a learning activity questionnaire and learning outcomes tests in the form of pretest and posttest. Before testing the hypothesis, the normality test was carried out with Kolmogorov Smirnov and the homogeneity test was carried out with the test of homogeneity of variance.